Immunization Using a Parametric Model of the Term Structure - Bravo, Jorge Miguel Ventura (2013)
In this paper, we develop a new immunization model based on a parametric specification of the term structure of interest rates. The model extends traditional duration analysis to account for both parallel and non-parallel term structure shifts that have an economic meaning. Contrary to most interest rate risk models, we analyse both first-order and second-order conditions for bond portfolio immunization and conclude that the key to successful protection will be to build up a bond portfolio such that the gradient of its future value is zero, and such that its Hessian matrix is positive semidefinite. In addition, we provide explicit formulae for new parametric interest rate risk measures and present alternative approaches to implement the immunization strategy. Furthermore, we provide useful expressions for the sensitivity of interest rate risk measures to changes in term structure shape parameters.